AKTIVITAS KEAGAMAAN MAHASISWA UNIVERSITAS NEGERI PADANG - Zein, Zainurni (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2012)
This research studied about students’ religious activities in Padang State University (UNP). These religious activities were meant to help the students develop good characters and attitude. However, reality showed contrast between these students’ behaviors and their religious values, such as frequently getting involved in student fights or doing any other amoral acts. Regarding the problem, this research aimed to observe the religious activities conducted by UNP’s students and describe the implementation of the activities. The design of this research was qualitative, with students conducting religious activities as the source of information. The instruments were observation, interviews and documentaries review. The research found that religious activities were conducted in the form of both intracurricular (included in the curriculum) and extracurricular which were managed and organized by religious education lecturers, and coordinated by the students. There were also other activities which were directly managed by the students of each faculty at UNP. Generally, those activities had similar visions and could give positive effect to students. Key words: students’ characters, attitudes, religious activities